2003
DOI: 10.4037/ajcc2003.12.3.220
|View full text |Cite
|
Sign up to set email alerts
|

A Multisite Survey of Suctioning Techniques and Airway Management Practices

Abstract: • Background Ventilator-associated pneumonia, common in critically ill patients, is associated with microaspiration of oropharyngeal secretions and may be related to suctioning and airway management practices.• Objectives To describe institutional policies and procedures related to closed-system suctioning and airway management of intubated patients, and to compare practices of registered nurses and respiratory therapists.• Methods A descriptive, comparative, multisite study of facilities that use closed-syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 39 publications
3
53
0
8
Order By: Relevance
“…While ETS is an important intervention when caring for critically ill patients, the practice surrounding ETS can vary widely between institutions and practitioners (Swartz et al 1996, Sole et al 2003 with much of that practice based on anecdote and routine rather than research (Paul Allen & Ostrow 2000, Thompson 2000, Day et al 2002b). This may partially have been influenced by a paucity of research evidence to guide practitioners in the care of a patient with an endotracheal tube (Thompson 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…While ETS is an important intervention when caring for critically ill patients, the practice surrounding ETS can vary widely between institutions and practitioners (Swartz et al 1996, Sole et al 2003 with much of that practice based on anecdote and routine rather than research (Paul Allen & Ostrow 2000, Thompson 2000, Day et al 2002b). This may partially have been influenced by a paucity of research evidence to guide practitioners in the care of a patient with an endotracheal tube (Thompson 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature that does exist raises concerns about the standard of ETS practice among nurses (Paul Allen & Ostrow 2000, Day et al 2002b). This evidence is predominantly American and based on descriptive, retrospective studies that focus on closed suctioning systems (Swartz et al 1996, Paul Allen & Ostrow 2000, Sole et al 2003. While such studies are important for describing and documenting the aspects of ETS practice, they have one primary limitation.…”
Section: Summary Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Studies aiming to determine the knowledge and skills of nurses regarding endotracheal suctioning methods (Ç elik & Elbas¸2000, Day et al 2001, Kelleher & Andrews 2008 indicate that their training for and experience of suctioning is far from sufficient. Moreover, nurses are inclined to rely on personal experience and ward routine to inform practice over any other source (Sole et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have suggested that aspiration of oropharyngeal secretions is an important factor in bacterial contamination of the upper respiratory tree. [50][51][52][53][54] Unfortunately, we did not have a marker for the aspiration of oropharyngeal secretions.…”
Section: Discussionmentioning
confidence: 99%